PEMENUHAN HAK ATAS KESEHATAN TERHADAP INTERNALLY DISPLACED PERSONS LANJUT USIA DALAM BENCANA TSUNAMI ACEH 2004 OLEH PEMERINTAH INDONESIA MENURUT HUKUM INTERNASIONAL: FULFILLMENT OF THE RIGHT TO HEALTH FOR INTERNALLY DISPLACED PERSONS OF THE ELDERLY IN THE 2004 ACEH TSUNAMI DISASTER BY THE GOVERNMENT OF INDONESIA ACCORDING TO INTERNATIONAL LAW - Surya, Muhammad Falih Nasywaan; Putri, Denyssa Jasmine Ardiansyah; Justinar, Jun (Fakultas Hukum Universitas Trisakti, 2022)
The earthquake that occurred on December 26, 2004 caused a tsunami that hit several countries, including Indonesia. The victims of the Aceh Tsunami were internally displaced persons who were the responsibility of the Indonesian government. This research was created to answer the question: what is the international refugee legal framework in order to fulfill the right to health for elderly IDPs? And what are the efforts of the Government of Indonesia in fulfilling the right to health for elderly IDPs in situations of natural disasters? This research is descriptive normative with secondary data and deductive conclusions. The results showed that protection for the elderly is spread across several international agreements related to human rights. The Government of Indonesia fulfills the right to health for IDPs for elderly victims of the Aceh tsunami in collaboration with IOM and UNHCR.